The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biology10121282
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Re-Evaluation of Evolutionary Rate of Powassan Virus Using Complete Genome Data

Abstract: In this paper, we revealed the genetic structure and migration history of the Powassan virus (POWV) reconstructed based on 25 complete genomes available in NCBI and ViPR databases (accessed in June 2021). The usage of this data set allowed us to perform a more precise assessment of the evolutionary rate of this virus. In addition, we proposed a simple Bayesian technique for the evaluation and visualization of ‘temporal signal dynamics’ along the phylogenetic tree. We showed that the evolutionary rate value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
2
6
2
Order By: Relevance
“…Our phylogenetic analysis supported the presence of two geographically separated DTV sublineages, consistent with prior reports ( Pesko et al. 2010 ; Anderson and Armstrong 2012 ; Bondaryuk et al. 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our phylogenetic analysis supported the presence of two geographically separated DTV sublineages, consistent with prior reports ( Pesko et al. 2010 ; Anderson and Armstrong 2012 ; Bondaryuk et al. 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Time-scaled phylogenetic analysis of DTV sequences indicated that the Northeast and Midwest sublineages last shared an MRCA approximately 1,200 years ago. Our results (time to most recent common ancestor (TMRCA) 1,184 years ago, 95 per cent HPD 770–1,658) were consistent with the results from an analysis of twenty-six full-genome sequences in 2019 (TMRCA 1,160 years ago, 95 per cent HPD 760–1,750) ( Bondaryuk et al. 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We estimate that the evolutionary rate of this clade is 8.25×10 −5 substitutions/site/year (95% highest posterior density [HPD] interval: [8.23-10.46×10 −5 ]; 95% HPD interval of the associated coefficient of variation: [0.48-0.75]). Our estimate is higher than previous estimated evolutionary rates for all Powassan viruses (3.3×10 −5 (23) ) and NS5 coding sequences (3.9×10 −5 -5.4×10 −5 (5, 24) ), but lower than previous estimates based on envelope coding sequences (2.2×10 −4 (5) ). This is likely a reflection of the recent emergence of lineage II in the region.…”
Section: Resultscontrasting
confidence: 85%
“…46 10 -5 ]). Our estimate is higher than previous estimated evolutionary rates for all × Powassan viruses (3.3 10 -5 ) 22 , and than previous estimates based on envelope (2.2 10 -4 ) 5 and × × NS5 coding sequences (3.9 10 -5 -5.4 10 -5 ) 5,23 , likely a reflection of the recent emergence of × × lineage II in the region. Our work increased the number of publicly available Powassan virus lineage II sequences by more than ten-fold, enabling us to better understand the patterns of emergence and spread in the northeastern United States.…”
Section: Powassan Virus Phylogenycontrasting
confidence: 79%